Abortion and women's roles in society: opinions from Tlaxcala, Mexico El aborto y el rol de las mujeres en la sociedad: resultados de una encuesta de opinión en Tlaxcala, México - Tia M Palermo; Kate S Wilson; Sandra G García; Claudia Díaz-Olavarrieta (Instituto Nacional de Salud Pública, 2010)
OBJECTIVE: We aim to assess the opinions of Mexicans in the state of Tlaxcala on abortion and other topics concerning women's reproductive health and status in society. MATERIAL AND METHODS: We summarize opinions on abortion and women's roles in society and perform logit regressions to assess characteristics correlated with support for abortion rights. RESULTS: A majority of respondents were against a woman's right to abortion when asked generally, but when asked about specific circumstances, a majority supported the right to abortion in five of the nine hypothetical circumstances proposed. In multivariate analysis, age, education, religion, religious service attendance, and views regarding women's roles in society had significant effects on support for the right to abortion. CONCLUSIONS: Our results demonstrate that residents of Tlaxcala view abortion as a personal decision and support a woman's right to abortion in more circumstances than currently allowed under state law. OBJETIVO: Describir opiniones sobre salud sexual y reproductiva, aborto y rol social de las mujeres entre un grupo de residentes de Tlaxcala, México. MATERIAL Y MÉTODOS: El análisis de regresión logística analizó características asociadas con una postura de apoyo al derecho al aborto. RESULTADOS: La mayoría no favoreció el derecho de las mujeres a interrumpir un embarazo cuando se preguntó de manera general. Al momento de circunscribirlo a circunstancias específicas, la mayoría estuvo a favor en cinco de las nueve de situaciones hipotéticas planteadas. En análisis multivariado, edad, escolaridad, religión, asistencia a servicios religiosos y opiniones sobre el rol social femenino fueron variables significativas del apoyo que se brinda a una mujer para ejercer su derecho a interrumpir un embarazo. CONCLUSIONES: Los residentes de Tlaxcala perciben el tema del aborto como una decisión personal y apoyan el derecho de una mujer a interrumpirlo especialmente bajo causales contempladas en la ley de Tlaxcala.